Effects of Airless Bodies’ Regolith Structures and of the Solar Wind’s Properties on the Backscattered Energetic Neutral Atoms Flux - S. Verkercke; J.-Y. Chaufray; F. Leblanc; E. M. Bringa; D. Tramontina; L. Morrissey; A. Woodson (The Planetary Science Journal, 2023)
The surfaces of airless planetary bodies, such as the Moon or Mercury, are covered with regoliths, which interact with the solar wind. The solar protons can either be absorbed by the surface or neutralized and reflected as hydrogen energetic neutral atoms (ENAs). The ENA flux is thought to depend mostly on the structure of the upper regolith layer. By using a model combining a Monte Carlo approach to describe a solar proton’s journey through the lunar surface with molecular dynamics to characterize its interactions with the regolith’s grains, we highlight the surface roughness as a key parameter that influences the backscattered H ENA flux. By considering spherical silica grains, the lunar regolith’s structure is described using the open-source code Large-scale Atomic/Molecular Massively Parallel Simulator (or LAMMPS), which allows a realistic description of grain-on-grain contacts. The roughness of the modeled regolith, characterized by the roughness ratio, is shown to be dictated by the surface energy and the grain-size distribution. This work shows that a rougher surface favors deeper penetration of the protons inside the regolith, which increases the number of collisions and thus decreases their reflected fraction. The angular distribution of the backscattered H ENAs is influenced by both the surface roughness and the solar zenith angle. We show that the angular distribution of the backscattered ENAs is anisotropic and is influenced by the regolith’s structure, which is consistent with Chandrayaan-1 measurements. This work aims for a better understanding of the interactions ongoing at this interface and intends to look into the possibility of deducing information on the surface structure solely from ENA flux measurements. Highlighting the key structural parameters influencing the ENA backscattering will also help the development of models of surface-bounded exospheres.